Intelligent Traffic Control (i-TC) for Road Construction - Mohd Nizam, Nurul Nazira; Zailani, Nurul Farhana; Mohd Rozaimi, Fatin Nur Syafiqah; Hairuddin, Muhammad Asraf; Khirul Ashar, Nur Dalila (2020)
Work operation in heavy construction site requires high safety level, which includes the management of the traffic congestion near the constructed road. Nowadays, many roads require maintenance or newly built construction thus disturb the road traffic, especially near the narrow road. This problem will cause traffic congestion from two opposite directions and hence the user should wait longer. To cater such problems, Intelligent Traffic Control (i-TC) was innovated for mitigating the purpose. With an improved characteristic, i.e. portable and easy operation, the product can be used at shuttle working sites with restricted road condition of one-directional road route. Our aims to construct a smart portable traffic light that can control the flow of the car at an affordable cost comprises of microcontroller, RF receiver and transmitter, and I/O accessories of the button and LED arrays. As results, this invention could increase productivity, shorten the required time and human intervention for traffic patrolling, and ultimately reduce the operating costs. The better coordination between two roadsides ensures a smoother traffic flow.